Changes in obstetric interventions and preterm birth during COVID‐19: A nationwide study from Iceland. (28th July 2021) - Einarsdóttir, Kristjana; Swift, Emma Marie; Zoega, Helga
Abstract: Introduction: Previous evidence has been conflicting regarding the effect of coronavirus disease 2019 (COVID‐19) pandemic lockdowns on obstetric intervention and preterm birth rates. The literature to date suggests potentially differential underlying mechanisms based on country economic setting. We aimed to study these outcomes in an Icelandic population where uniform lockdown measures were implemented across the country. Material and methods: The study included all singleton births ( n  = 20 680) during 2016–2020 identified from the population‐based Icelandic Medical Birth Register. We defined two lockdown periods during March–May and October–December in 2020 according to government implemented nationwide lockdown. We compared monthly rates of cesarean section, induction of labor and preterm birth during lockdown with the same time periods in the 4 previous years (2016–2019) using logit binomial regression adjusted for confounders. Results: Our results indicated a reduction in the overall cesarean section rate, which was mainly evident for elective cesarean section, both during the first (adjusted odd ratio [aOR] 0.71, 95% CI 0.51–0.99) and second (aOR 0.72, 95% CI 0.52–0.99) lockdown periods, and not for emergency cesarean section. No change during lockdown was observed in induction of labor. Our results also suggested a reduction in the overall preterm birth rate during the first lockdown (aOR 0.69, 95% CI 0.49–0.97) and in the months immediately following the lockdown (June–September) (aOR 0.67, 95% CI 0.49–0.89). The reduction during the first lockdown was mainly evident for medically indicated preterm birth (although not statistically significant) and the reduction during June–September was mainly evident for spontaneous preterm birth. Conclusions: This study suggested a reduction in elective cesarean section during COVID‐19 lockdown, possibly reflecting changes in prioritization of non‐urgent health care during lockdown. We also found a reduction in overall preterm birth during the first lockdown and spontaneous preterm birth following the first lockdown, but further research is needed to shed light on the underlying mechanisms for these findings.